Impact of EMI to Multilingual Learners at Secondary Level Students - Rai, Himan (International Journal of Educational and Life Sciences, 2023)
The study entitled as the impact of EMI to multilingual learners at secondary level education is based on qualitative research design. This paper tries to find out impact of EMI in secondary level students and its effects in students’ indigenous knowledge into multilingual class room. To conduct study, both primary and secondary sources of data collection procedure have been analysed clearly. For its primary source, interview was conducted with the English teachers, parents and students to find out impact of EMI towards students’ indigenous knowledge in multi lingual class room. And, for secondary sources of data collection, various many different policies, education act, SSDP, SSRP, research-based articles, and other related information from various websites have been analysed and reviewed. The result of the study included that all the participants viewed impact of EMI in secondary level education has more limitations than merits as the students’ indigenous knowledge differs among them in multilingual classroom. There are many mother tongue interferences in teaching learning. And it is found that there are many more things to be improved for betterment of the secondary level school education; conducting seminar, workshop or conference which enhance effectiveness of EMI in secondary level education